Drosophila Model for Studying Gut Microbiota in Behaviors and Neurodegenerative Diseases - Meng-Hsuan Chiang; Shuk-Man Ho; Hui-Yu Wu; Yu-Chun Lin; Wan-Hua Tsai; Tony Wu; Chih-Ho Lai; Chia-Lin Wu (Biomedicines, 2022)
Mounting evidence indicates that the gut microbiota is linked to several physiological processes and disease development in mammals; however, the underlying mechanisms remained unexplored mostly due to the complexity of the mammalian gut microbiome. The fruit fly, Drosophila melanogaster, is a valuable animal model for studying host-gut microbiota interactions in translational aspects. The availability of powerful genetic tools and resources in Drosophila allowed the scientists to unravel the mechanisms by which the gut microbes affect fitness, health, and behavior of their hosts. Drosophila models have been extensively used not only to study animal behaviors (i.e., courtship, aggression, sleep, and learning & memory), but also some human related neurodegenerative diseases (i.e., Alzheimer’s disease and Parkinson’s disease) in the past. This review comprehensively summarizes the current understanding of the gut microbiota of Drosophila and its impact on fly behavior, physiology, and neurodegenerative diseases.